High-thermal-conductivity radiation refrigeration coating for 5G communication base station cabinet and preparation method of high-thermal-conductivity radiation refrigeration coating
By constructing a continuous SiC@BN/TiB2 fiber skeleton, a star-shaped calcium titanate and magnesium fluoride shell, and holmium/ytterbium co-doped calcium fluoride nanosheets, the heat dissipation problem of 5G communication base station cabinets under high temperature and extreme climate was solved, achieving efficient and stable heat dissipation performance.
Patent Information
- Application Number
- CN202511482375.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-16
- Publication Date
- 2025-12-02
- Estimated Expiration
- 2045-10-16
AI Technical Summary
Existing thermal coatings for 5G communication base station cabinets are difficult to dissipate heat effectively under high temperature and extreme climates, leading to device performance drift, communication interruption, or irreversible failure. Existing coatings also have problems such as limited improvement in thermal conductivity, increased brittleness, easy cracking, and low emissivity.
A continuous SiC@BN/TiB2 fiber skeleton is generated by three-stage calcination. Combined with star-shaped calcium titanate and magnesium fluoride shells, the morphology is designed for multiple scattering and refractive index step interface. Holmium/ytterbium co-doped calcium fluoride nanosheets are introduced for energy conversion, constructing a longitudinal heat conduction and transverse heat dissipation network and a multi-level reflection/radiation interface. The coating is uniformly dispersed in methylphenyl silicone resin to form a high-efficiency heat dissipation coating.
It achieves efficient and reliable heat dissipation performance under high temperature and extreme climate conditions, and improves the thermal conductivity, reflectivity and radiation of the coating to ensure the stable operation of the cabinet.
Abstract
Description
Technical Field
[0001] This invention belongs to the field of coating technology and relates to a high thermal conductivity radiation cooling coating for 5G communication base station cabinets and its preparation method. Background Technology
[0002] With the rapid rollout of 5G networks, macro base stations, micro base stations, and even indoor distributed antenna systems are constantly evolving towards "high power, high integration, and lightweight." On the one hand, RF power amplifiers, power modules, and high-speed processing chips are being compressed into smaller volumes, resulting in exponentially increasing power consumption per unit area. On the other hand, to reduce construction costs, operators tend to mount entire equipment racks directly on building exteriors or tower crossarms, exposing them to extreme conditions such as high temperatures for extended periods. If heat dissipation is not timely, components will experience performance drift, communication interruptions, or even irreversible failure.
[0003] Current passive heat dissipation coatings generally follow two technical routes: one is to incorporate high thermal conductivity insulating particles into a polymer matrix, utilizing the intrinsic thermal conductivity of the filler to increase the overall thermal diffusivity of the system; the other is to introduce high reflectivity or high emissivity components to achieve radiative cooling by enhancing solar light scattering or mid-infrared emission. However, both types of coatings have shortcomings. For thermally conductive fillers, the particles have random point contacts, and heat flow needs to "jump" between interfaces multiple times to be transferred. Interface phonon scattering and thermal resistance severely weaken the improvement of macroscopic thermal conductivity. At the same time, high filler content leads to increased coating viscosity and brittleness, making it prone to cracking and peeling during thermal cycling or mechanical vibration. For optical coatings, although titanium dioxide can generate strong scattering in the visible light band, its own infrared emissivity is low, making it difficult to effectively release heat through atmospheric windows; silicon dioxide, on the other hand, cannot meet the dual requirements of solar reflection and infrared radiation. Summary of the Invention
[0004] To address the aforementioned problems, the present invention aims to provide a high thermal conductivity radiation cooling coating for 5G communication base station cabinets and its preparation method. This application constructs a three-stage calcined SiC@BN / TiB2 continuous fiber as a longitudinal thermally conductive framework, firmly bonded to resin with a silane coupling agent; utilizes star-shaped calcium titanate and its edge-grown in-situ magnesium fluoride shell, achieving strong reflection in the ultraviolet to mid-infrared region and improving weather resistance through morphological multiple scattering and refractive index stepped interfaces; introduces holmium / ytterbium co-doped calcium fluoride nanosheets, supplementing thermal conductivity, enhancing near-infrared scattering, and converting near-infrared heat into long-wave radiation that can be released through atmospheric windows via energy transfer; the entire filler system is uniformly dispersed in methylphenyl silicone resin, forming a micro-nano composite roughness under the synergistic effect of dispersants and leveling agents, constructing a multi-level reflection / radiation interface between air sandwich and low-refractive-index particles. Through the synergistic interaction of longitudinal continuous thermal conduction pathways, lateral heat dissipation network, optical multiple scattering, and energy-downward radiation, efficient and long-term reliable heat dissipation performance is achieved under the support of a stable chemical bond network.
[0005] To achieve this objective, the present invention adopts the following technical solution:
[0006] In a first aspect, the present invention provides a method for preparing a high thermal conductivity radiation cooling coating for 5G communication base station cabinets, the method comprising:
[0007] S1: Polycarbosilane, boric acid, isopropyl titanate and melamine are dissolved in a mixed solvent and stirred at room temperature to obtain a preliminary spinning solution. After filtration, a precursor fiber membrane is spun to obtain a precursor fiber membrane. The precursor fiber membrane is placed in air and then calcined and naturally cooled to obtain a preliminary fiber skeleton. The precursor fiber membrane is then impregnated in an ethanol-water solution of a silane coupling agent and dried to obtain a SiC@BN / TiB2 three-phase fiber skeleton.
[0008] S2: Prepare calcium hydroxide dispersion, add titanium chloride under ice bath and adjust pH with potassium hydroxide, perform hydrothermal reaction, cool, centrifuge, wash with water and vacuum dry to obtain star-shaped calcium titanate powder; disperse magnesium nitrate and ammonium fluoride in deionized water, add calcium titanate powder to obtain reaction solution A, stir, filter, dry and pulverize and air calcinate to obtain calcium titanate / magnesium fluoride composite material.
[0009] S3: Calcium nitrate, holmium nitrate and ytterbium nitrate were dispersed in deionized water to obtain a mixed dispersion. Sodium fluoride was added, stirred, centrifuged, washed and dried to obtain a mixed precursor. It was placed in a quartz boat for crystallization and naturally cooled to obtain holmium / ytterbium co-doped calcium fluoride nanosheets.
[0010] S4: SiC@BN / TiB2 three-phase fiber skeleton and methylphenyl silicone resin are placed in a planetary vacuum stirring vessel and stirred to obtain a premixed base liquid. Calcium titanate / magnesium fluoride composite material and holmium / ytterbium co-doped calcium fluoride nanosheets are added and dispersed evenly. Then, methylphenyl silicone resin, KH-550, BYK-A530, FC-4430 and propylene glycol methyl ether acetate are added to obtain a pre-coating liquid. The viscosity is adjusted, and the mixture is vacuum degassed and filtered to obtain a high thermal conductivity radiation cooling coating for 5G communication base station cabinets.
[0011] As a preferred technical solution of the present invention, in step S1, the mass ratio of polycarbosilane to boric acid is (17-19):(1.4-1.6), for example, it can be (17, 17.2, 17.4, 17.6, 17.8, 18, 18.2, 18.4, 18.6, 18.8 or 19):(1.4, 1.42, 1.44, 1.46, 1.48, 1.50, 1.52, 1.54, 1.56, 1.58 or 1.6), but it is not limited to the listed values, and other unlisted values within this range are also applicable.
[0012] In some optional embodiments, the mass ratio of the polycarbosilane to isopropyl titanate is (17-19):(0.95-1.05), for example, it can be (17, 17.2, 17.4, 17.6, 17.8, 18, 18.2, 18.4, 18.6, 18.8 or 19):(0.95, 0.96, 0.97, 0.98, 0.99, 1.00, 1.01, 1.02, 1.03, 1.04 or 1.05), but is not limited to the listed values, other unlisted values within this range are also applicable.
[0013] In some optional embodiments, the mass ratio of polycarbosilane to melamine is (17-19):(0.75-0.85), for example, it can be (17, 17.2, 17.4, 17.6, 17.8, 18, 18.2, 18.4, 18.6, 18.8 or 19):(0.75, 0.76, 0.77, 0.78, 0.79, 0.80, 0.81, 0.82, 0.83, 0.84 or 0.85), but is not limited to the listed values, other unlisted values within this range are also applicable.
[0014] In some optional embodiments, the mass ratio of DMF to THF in the mixed solvent is 1:(1-1.2), for example, it can be 1:1.00, 1:1.02, 1:1.04, 1:1.06, 1:1.08, 1:1.10, 1:1.12, 1:1.14, 1:1.16, 1:1.18 or 1:1.20, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0015] In some optional embodiments, the mass ratio of the polycarbosilane to DMF is (17-19):(38-42), for example, it can be (17, 17.2, 17.4, 17.6, 17.8, 18, 18.2, 18.4, 18.6, 18.8 or 19):(38, 38.4, 38.8, 39.2, 39.6, 40, 40.4, 40.8, 41.2, 41.6 or 42), but is not limited to the listed values, other unlisted values within this range are also applicable.
[0016] In some optional embodiments, in step S1, the stirring speed is 350-450 rpm, for example, it can be 350 rpm, 360 rpm, 370 rpm, 380 rpm, 390 rpm, 400 rpm, 410 rpm, 420 rpm, 430 rpm, 440 rpm or 450 rpm, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0017] In some optional embodiments, the stirring time in step S1 is 1.5-2.5h, for example, it can be 1.5h, 1.6h, 1.7h, 1.8h, 1.9h, 2.0h, 2.1h, 2.2h, 2.3h, 2.4h or 2.5h, but is not limited to the listed values. Other unlisted values within this range are also applicable.
[0018] In some optional embodiments, the precursor fiber membrane is left in air for 1.5-3 hours, for example, 1.5 hours, 1.65 hours, 1.80 hours, 1.95 hours, 2.10 hours, 2.25 hours, 2.40 hours, 2.55 hours, 2.70 hours, 2.85 hours, or 3.0 hours, but is not limited to the listed values; other unlisted values within this range are also applicable.
[0019] When the precursor fiber membrane is placed in air and then calcined, the first stage of calcination atmosphere is air.
[0020] In some optional embodiments, the heating rate of the first stage is 1-3℃ / min, for example, it can be 1.0℃ / min, 1.2℃ / min, 1.4℃ / min, 1.6℃ / min, 1.8℃ / min, 2.0℃ / min, 2.2℃ / min, 2.4℃ / min, 2.6℃ / min, 2.8℃ / min or 3.0℃ / min, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0021] In some optional embodiments, the first-stage calcination temperature of the precursor fiber membrane after being placed in air and then calcined is 240-260°C, for example, 240°C, 242°C, 244°C, 246°C, 248°C, 250°C, 252°C, 254°C, 256°C, 258°C or 260°C, but is not limited to the listed values, and other unlisted values within this range are also applicable.
[0022] In some optional embodiments, the first stage calcination time of the precursor fiber membrane after being placed in air and then calcined is 1.5-2.5h, for example, it can be 1.5h, 1.6h, 1.7h, 1.8h, 1.9h, 2.0h, 2.1h, 2.2h, 2.3h, 2.4h or 2.5h, but is not limited to the listed values, and other unlisted values within this range are also applicable.
[0023] The precursor fiber membrane is placed in air and then calcined in the second stage under an argon atmosphere.
[0024] In some optional embodiments, the argon flow rate during the second stage of calcination after the precursor fiber membrane is placed in air is 180-220 mL / min, for example, it can be 180 mL / min, 184 mL / min, 188 mL / min, 192 mL / min, 196 mL / min, 200 mL / min, 204 mL / min, 208 mL / min, 212 mL / min, 216 mL / min or 220 mL / min, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0025] In some optional embodiments, the second-stage heating rate during calcination of the precursor fiber membrane after being placed in air is 4-6 °C / min, for example, it can be 4.0 °C / min, 4.2 °C / min, 4.4 °C / min, 4.6 °C / min, 4.8 °C / min, 5.0 °C / min, 5.2 °C / min, 5.4 °C / min, 5.6 °C / min, 5.8 °C / min or 6.0 °C / min, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0026] In some optional embodiments, the second-stage calcination temperature of the precursor fiber membrane after being placed in air and then calcined is 580-620°C, for example, 580°C, 584°C, 588°C, 592°C, 596°C, 600°C, 604°C, 608°C, 612°C, 616°C, or 620°C, but is not limited to the listed values; other unlisted values within this range are also applicable.
[0027] In some optional embodiments, the second-stage calcination time of the precursor fiber membrane after being placed in air and then calcined is 0.4-0.6 h, for example, it can be 0.40 h, 0.42 h, 0.44 h, 0.46 h, 0.48 h, 0.50 h, 0.52 h, 0.54 h, 0.56 h, 0.58 h or 0.60 h, but is not limited to the listed values, and other unlisted values within this range are also applicable.
[0028] When the precursor fiber membrane is placed in air and then calcined, the third stage calcination atmosphere is a mixture of ammonia and argon, with a volume ratio of ammonia to argon of 1:4.
[0029] In some optional embodiments, the third-stage mixing gas flow rate during calcination of the precursor fiber membrane after being placed in air is 450-550 mL / min, for example, it can be 450 mL / min, 460 mL / min, 470 mL / min, 480 mL / min, 490 mL / min, 500 mL / min, 510 mL / min, 520 mL / min, 530 mL / min, 540 mL / min or 550 mL / min, but is not limited to the listed values, and other unlisted values within this range are also applicable.
[0030] In some optional embodiments, the third-stage heating rate during calcination of the precursor fiber membrane after being placed in air is 8-12℃ / min, for example, it can be 8.0℃ / min, 8.4℃ / min, 8.8℃ / min, 9.2℃ / min, 9.6℃ / min, 10.0℃ / min, 10.4℃ / min, 10.8℃ / min, 11.2℃ / min, 11.6℃ / min or 12.0℃ / min, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0031] In some optional embodiments, the third-stage calcination temperature of the precursor fiber membrane after being placed in air and then calcined is 1050-1150°C, for example, it can be 1050°C, 1060°C, 1070°C, 1080°C, 1090°C, 1100°C, 1110°C, 1120°C, 1130°C, 1140°C or 1150°C, but is not limited to the listed values, and other unlisted values within this range are also applicable.
[0032] In some optional embodiments, the third-stage calcination time of the precursor fiber membrane after being placed in air and then calcined is 0.8-1.2h, for example, it can be 0.80h, 0.84h, 0.88h, 0.92h, 0.96h, 1.00h, 1.04h, 1.08h, 1.12h, 1.16h or 1.20h, but is not limited to the listed values, and other unlisted values within this range are also applicable.
[0033] In some optional embodiments, the silane coupling agent is KH-550, and the mass fraction of the ethanol aqueous solution of the silane coupling agent is 0.4-0.6 wt%, for example, it can be 0.40 wt%, 0.42 wt%, 0.44 wt%, 0.46 wt%, 0.48 wt%, 0.50 wt%, 0.52 wt%, 0.54 wt%, 0.56 wt%, 0.58 wt%, or 0.60 wt%, but is not limited to the listed values, and other unlisted values within this range are also applicable.
[0034] In some optional embodiments, the immersion time is 25-35 min, for example, it can be 25 min, 26 min, 27 min, 28 min, 29 min, 30 min, 31 min, 32 min, 33 min, 34 min or 35 min, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0035] In some optional embodiments, in step S1, the drying temperature is 110-130°C, for example, it can be 110°C, 112°C, 114°C, 116°C, 118°C, 120°C, 122°C, 124°C, 126°C, 128°C or 130°C, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0036] In some optional embodiments, the drying time in step S1 is 0.4-0.6h, for example, it can be 0.40h, 0.42h, 0.44h, 0.46h, 0.48h, 0.50h, 0.52h, 0.54h, 0.56h, 0.58h or 0.60h, but is not limited to the listed values. Other unlisted values within this range are also applicable.
[0037] As a preferred technical solution of the present invention, in step S2, the mass ratio of calcium hydroxide to deionized water is (7-7.8):(190-210), for example, it can be (7, 7.08, 7.16, 7.24, 7.32, 7.40, 7.48, 7.56, 7.64, 7.72 or 7.80):(190, 192, 194, 196, 198, 200, 202, 204, 206, 208 or 210), but it is not limited to the listed values, and other unlisted values within this range are also applicable.
[0038] In some optional embodiments, the pH of the calcium hydroxide dispersion is adjusted to 10.5-11.5 using potassium hydroxide after the addition of titanium chloride. For example, the pH may be 10.5, 10.6, 10.7, 10.8, 10.9, 11.0, 11.1, 11.2, 11.3, 11.4 or 11.5, but is not limited to the listed values. Other unlisted values within this range are also applicable.
[0039] In some optional embodiments, the mass ratio of titanium chloride to calcium hydroxide is (7-7.8):(9-10), for example, it can be (7, 7.08, 7.16, 7.24, 7.32, 7.40, 7.48, 7.56, 7.64, 7.72 or 7.80):(9.0, 9.1, 9.2, 9.3, 9.4, 9.5, 9.6, 9.7, 9.8, 9.9 or 10.0), but is not limited to the listed values, other unlisted values within this range are also applicable.
[0040] In some optional embodiments, the hydrothermal reaction temperature is 170-190°C, for example, it can be 170°C, 172°C, 174°C, 176°C, 178°C, 180°C, 182°C, 184°C, 186°C, 188°C or 190°C, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0041] In some optional embodiments, the hydrothermal reaction time is 6-10 h, for example, it can be 6.0 h, 6.4 h, 6.8 h, 7.2 h, 7.6 h, 8.0 h, 8.4 h, 8.8 h, 9.2 h, 9.6 h or 10.0 h, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0042] In some optional embodiments, the mass ratio of magnesium nitrate, ammonium fluoride, and deionized water is (2.9-3.3):(1-1.2):(35-45), for example, it can be (2.90, 2.94, 2.98, 3.02, 3.06, 3.10, 3.14, 3.18, 3.22, 3.26, or 3.30):(1.00, 1.02, 1.04, 1.06, 1.08, 1.10, 1.12, 1.14, 1.16, 1.18, or 1.20):(35, 36, 37, 38, 39, 40, 41, 42, 43, 44, or 45), but is not limited to the listed values, and other unlisted values within this range are also applicable.
[0043] In some optional embodiments, the mass ratio of calcium titanate powder to magnesium nitrate is (2.9-3.3):(9.5-10.5), for example, it can be (2.90, 2.94, 2.98, 3.02, 3.06, 3.10, 3.14, 3.18, 3.22, 3.26 or 3.30):(9.5, 9.6, 9.7, 9.8, 9.9, 10.0, 10.1, 10.2, 10.3, 10.4 or 10.5), but is not limited to the listed values, other unlisted values within this range are also applicable.
[0044] In some optional embodiments, in step S2, the stirring temperature is 65-75°C, for example, it can be 65°C, 66°C, 67°C, 68°C, 69°C, 70°C, 71°C, 72°C, 73°C, 74°C or 75°C, but is not limited to the listed values. Other unlisted values within this range are also applicable.
[0045] In some optional embodiments, the stirring time in step S2 is 0.8-1.2h, for example, it can be 0.80h, 0.84h, 0.88h, 0.92h, 0.96h, 1.00h, 1.04h, 1.08h, 1.12h, 1.16h or 1.20h, but is not limited to the listed values. Other unlisted values within this range are also applicable.
[0046] In some optional embodiments, the air calcination temperature is 430-470°C, for example, it can be 430°C, 434°C, 438°C, 442°C, 446°C, 450°C, 454°C, 458°C, 462°C, 466°C or 470°C, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0047] In some optional embodiments, the air calcination time is 0.8-1.2h, for example, it can be 0.80h, 0.84h, 0.88h, 0.92h, 0.96h, 1.00h, 1.04h, 1.08h, 1.12h, 1.16h or 1.20h, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0048] In a preferred embodiment of the present invention, in step S3, the mass ratio of calcium nitrate, holmium nitrate, ytterbium nitrate, and deionized water is (11.2-12.4):(0.26-0.30):(1.55-1.71):(90-110), for example, (11.2, 11.32, 11.44, 11.56, 11.68, 11.80, 11.92, 12.04, 12.16, 12.28, or 12.4):(0.26, 0.264, 0.268, 0.27). 2. 0.276, 0.280, 0.284, 0.288, 0.292, 0.296 or 0.30: (1.55, 1.566, 1.582, 1.598, 1.614, 1.630, 1.646, 1.662, 1.678, 1.694 or 1.710): (90, 92, 94, 96, 98, 100, 102, 104, 106, 108 or 110), but not limited to the listed values; other unlisted values within this range also apply.
[0049] In some optional embodiments, the mass ratio of calcium nitrate to sodium fluoride is (11.2-12.4):(11.5-13.5), for example, it can be (11.2, 11.32, 11.44, 11.56, 11.68, 11.80, 11.92, 12.04, 12.16, 12.28 or 12.4):(11.5, 11.7, 11.9, 12.1, 12.3, 12.5, 12.7, 12.9, 13.1, 13.3 or 13.5), but is not limited to the listed values, other unlisted values within this range are also applicable.
[0050] In some optional embodiments, the temperature at which sodium fluoride is added to the mixed dispersion is 55-65°C, for example, 55°C, 56°C, 57°C, 58°C, 59°C, 60°C, 61°C, 62°C, 63°C, 64°C or 65°C, but is not limited to the listed values, and other unlisted values within this range are also applicable.
[0051] In some optional embodiments, in step S3, the stirring speed is 250-350 rpm, for example, it can be 250 rpm, 260 rpm, 270 rpm, 280 rpm, 290 rpm, 300 rpm, 310 rpm, 320 rpm, 330 rpm, 340 rpm or 350 rpm, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0052] In some optional embodiments, the stirring time in step S3 is 1.5-2.5h, for example, it can be 1.5h, 1.6h, 1.7h, 1.8h, 1.9h, 2.0h, 2.1h, 2.2h, 2.3h, 2.4h or 2.5h, but is not limited to the listed values. Other unlisted values within this range are also applicable.
[0053] The crystallization atmosphere is argon;
[0054] In some optional embodiments, the argon flow rate is 250-350 mL / min, for example, it can be 250 mL / min, 260 mL / min, 270 mL / min, 280 mL / min, 290 mL / min, 300 mL / min, 310 mL / min, 320 mL / min, 330 mL / min, 340 mL / min or 350 mL / min, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0055] In some optional embodiments, the temperature rise rate during crystallization is 4-6 °C / min, for example, it can be 4.0 °C / min, 4.2 °C / min, 4.4 °C / min, 4.6 °C / min, 4.8 °C / min, 5.0 °C / min, 5.2 °C / min, 5.4 °C / min, 5.6 °C / min, 5.8 °C / min or 6.0 °C / min, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0056] In some optional embodiments, the crystallization temperature is 330-370°C, for example, it can be 330°C, 334°C, 338°C, 342°C, 346°C, 350°C, 354°C, 358°C, 362°C, 366°C or 370°C, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0057] In some optional embodiments, the crystallization time is 0.8-1.2h, for example, it can be 0.80h, 0.84h, 0.88h, 0.92h, 0.96h, 1.00h, 1.04h, 1.08h, 1.12h, 1.16h or 1.20h, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0058] As a preferred technical solution of the present invention, in step S4, the mass ratio of the SiC@BN / TiB2 three-phase fiber skeleton to methylphenyl silicone resin is (28-32):(54-56), for example, it can be (28, 28.4, 28.8, 29.2, 29.6, 30, 30.4, 30.8, 31.2, 31.6 or 32):(54, 54.2, 54.4, 54.6, 54.8, 55.0, 55.2, 55.4, 55.6, 55.8 or 56), but it is not limited to the listed values, and other unlisted values within this range are also applicable.
[0059] In some optional embodiments, in step S4, the stirring speed is 450-550 rpm, for example, it can be 450 rpm, 460 rpm, 470 rpm, 480 rpm, 490 rpm, 500 rpm, 510 rpm, 520 rpm, 530 rpm, 540 rpm or 550 rpm, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0060] In some optional embodiments, in step S4, the stirring vacuum degree is -0.04 to -0.06 MPa, for example, it can be -0.060 MPa, -0.058 MPa, -0.056 MPa, -0.054 MPa, -0.052 MPa, -0.050 MPa, -0.048 MPa, -0.046 MPa, -0.044 MPa, -0.042 MPa or -0.040 MPa, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0061] In some optional embodiments, the stirring time in step S4 is 4-6 min, for example, it can be 4 min, 4.2 min, 4.4 min, 4.6 min, 4.8 min, 5.0 min, 5.2 min, 5.4 min, 5.6 min, 5.8 min or 6 min, but is not limited to the listed values, other unlisted values within this range are also applicable.
[0062] In some optional embodiments, the mass ratio of the calcium titanate / magnesium fluoride composite material to the methylphenyl silicone resin is (23-27):(54-56), for example, it can be (23, 23.4, 23.8, 24.2, 24.6, 25.0, 25.4, 25.8, 26.2, 26.6 or 27):(54, 54.2, 54.4, 54.6, 54.8, 55.0, 55.2, 55.4, 55.6, 55.8 or 56), but is not limited to the listed values, other unlisted values within this range are also applicable.
[0063] In some optional embodiments, the mass ratio of the holmium / ytterbium co-doped calcium fluoride nanosheets to methylphenyl silicone resin is (7-9):(54-56), for example, it can be (7.0, 7.2, 7.4, 7.6, 7.8, 8.0, 8.2, 8.4, 8.6, 8.8 or 9.0):(54, 54.2, 54.4, 54.6, 54.8, 55.0, 55.2, 55.4, 55.6, 55.8 or 56), but is not limited to the listed values, other unlisted values within this range are also applicable.
[0064] In some optional embodiments, the mass ratio of the methylphenyl silicone resin, the supplemented methylphenyl silicone resin, KH-550, BYK-A530, FC-4430 to propylene glycol methyl ether acetate is (54-56):(17-21):(0.40-0.60):(0.15-0.25):(0.25-0.35):(8-12), for example, it can be (54, 54.2, 54.4, 54.6, 54.8, 55.0, 55.2, 55.4, 55.6, 55.8 or 56):(17, 17.4, 17.8, 18.2, 18.6, 19.0, 19.4, 19.8, 20.2, 20.6 or 21):(0.40, 0. 42, 0.44, 0.46, 0.48, 0.50, 0.52, 0.54, 0.56, 0.58 or 0.60): (0.15, 0.16, 0.17, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24 or 0.25): (0.25, 0.26, 0.27, 0.28, 0.29, 0.30, 0.31, 0.32, 0.33, 0.34 or 0.35): (8.0, 8.4, 8.8, 9.2, 9.6, 10.0, 10.4, 10.8, 11.2, 11.6 or 12.0), but not limited to the listed values; other unlisted values within this range also apply.
[0065] In some alternative embodiments, the viscosity is adjusted to 4-6 Pa·s, for example, 4.0 Pa·s, 4.2 Pa·s, 4.4 Pa·s, 4.6 Pa·s, 4.8 Pa·s, 5.0 Pa·s, 5.2 Pa·s, 5.4 Pa·s, 5.6 Pa·s, 5.8 Pa·s, or 6.0 Pa·s, but is not limited to the listed values; other unlisted values within this range are also applicable.
[0066] Secondly, the present invention provides a high thermal conductivity radiation cooling coating for 5G communication base station cabinets.
[0067] In this application, after polycarbosilane is spun into continuous fibers, it undergoes three stages of calcination: pre-oxidation, inert gas pyrolysis, and ammoniation and boronization. This sequentially completes cross-linking and shaping, amorphous silicon carbide formation, and silicon carbide crystallization, simultaneously generating boron nitride and titanium diboride in situ, forming a three-phase fiber skeleton. Silicon carbide provides the main heat conduction channels, while the layered bonding of boron nitride forms additional in-plane phonon fast channels within the fiber, simultaneously reducing the overall dielectric constant. The lattice matching of titanium diboride and silicon carbide allows for the formation of phonon bridges between the two phases, further reducing interfacial thermal resistance. After impregnation with a silane coupling agent, the hydroxyl-siloxane network on the fiber skeleton's surface can condense with the resin and fillers, thereby enhancing the chemical bonding between the skeleton and the matrix, laying the foundation for the "continuous thermal conductivity" of subsequent coatings.
[0068] In this application, calcium hydroxide and titanium chloride react in an alkaline environment to form a multi-faceted, hollow star-shaped calcium titanate structure. This morphology can generate composite scattering in the ultraviolet-near-infrared band, thus efficiently reflecting solar energy. Subsequently, fluoride and magnesium ions are used to generate a magnesium fluoride shell in situ on the edges of the calcium titanate, forming a stepped interface with a sudden change in refractive index. The change in refractive index not only further enhances scattering but also brings higher mid-infrared emissivity; moreover, magnesium fluoride itself has extremely low visible-near-infrared absorption and excellent weather resistance, which can improve the durability of the coating.
[0069] This application introduces calcium fluoride crystals, which have a wide bandgap and low phonon energy, making them an ideal far-infrared radiation matrix. Through conditional control, they are induced to grow into thin sheets along a layered orientation. These sheets can be stacked in-plane to supplement lateral heat conduction channels and produce strong scattering of near-infrared light. Furthermore, after ytterbium absorbs common near-infrared thermal radiation, it transfers energy to holmium, which then radiates out at a longer wavelength (falling within the atmospheric transmission window). Through co-doping of holmium and ytterbium, near-infrared heat in the environment near the cabinet can also be "moved down" and emitted.
[0070] In this application, methylphenyl silicone resin, a three-phase fiber skeleton, calcium titanate / magnesium fluoride composite material, and holmium / ytterbium co-doped calcium fluoride nanosheets are uniformly dispersed in the matrix to avoid thermal resistance and optical defects caused by agglomeration. Dispersant BYK-A530 and leveling agent FC-4430 further reduce interfacial tension and ensure all-directional overlap of the filler. At the same time, the moderate system viscosity is conducive to defoaming and allows the coating to form a micron-nano-scale composite roughness during spraying. The roughness is constructed through the synergistic effect of "air interlayer-low refractive index particles" to create a multi-level reflection / radiation interface.
[0071] Synergistic enhancement also exists in this application. In the longitudinal direction of the coating, the SiC@BN / TiB2 three-phase fiber skeleton is tightly coupled with the resin matrix, forming a rapid heat conduction channel that runs through the metal wall to the outer surface; in the transverse direction of the coating, the lamellar calcium fluoride and calcium titanate / magnesium fluoride composite material intertwine, diffusing hot spots and improving mechanical integrity; at the light management level, the multi-level roughness-refractive index gradient enhances solar reflection, and calcium fluoride and titanate together provide high radiation through the atmospheric window; the holmium / ytterbium energy level conversion further converts and outputs near-infrared heat from the environment; at the interface level, the coupling agent and methylphenyl silicone resin form a stable chemical bond network, ensuring the continuity of thermal conductivity and the integrity of the structure.
[0072] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0073] This application utilizes polycarbosilane spinning followed by three-stage calcination to generate a continuous fiber skeleton containing silicon carbide, boron nitride, and titanium diboride in one step. Silicon carbide provides the main thermal conductivity, layered boron nitride provides additional in-plane phonon fast channels within the fiber and reduces the dielectric constant, and titanium diboride forms phonon bridges with silicon carbide lattice matching to reduce interfacial thermal resistance. Subsequently, a silane coupling agent is used to activate the fiber surface, stabilizing the bond between the inorganic skeleton and the organic matrix and ensuring the continuity of the thermally conductive network.
[0074] This application involves reacting calcium hydroxide with titanium chloride under alkaline conditions to generate hollow, multi-faceted star-shaped calcium titanate, which reflects ultraviolet to near-infrared light through a morphology-multiple scattering mechanism. Subsequently, a magnesium fluoride shell is deposited in situ on its edges to form a refractive index stepped interface, which further enhances scattering and mid-infrared radiation. The low light absorption and high weather resistance of magnesium fluoride also improve the long-term stability of the coating.
[0075] This application utilizes calcium fluoride nanosheets with a wide bandgap and low phonon energy as a far-infrared radiation matrix, which can form a lateral heat-conducting channel and generate strong scattering of near-infrared light. At the same time, ytterbium-holmium co-doping is adopted, in which ytterbium ions first absorb near-infrared energy and transfer it to holmium ions, and then holmium ions release it through radiation at a longer wavelength that is in the atmospheric window, thereby realizing the downward displacement and effective emission of near-infrared heat in the environment.
[0076] This application uses methylphenyl silicone resin as a polysiloxane, which has thermal stability, UV resistance, and damp heat resistance. A dispersant is used to uniformly distribute the three-phase fiber skeleton, calcium titanate / magnesium fluoride composite material, and holmium / ytterbium co-doped calcium fluoride nanosheets, eliminating the thermal resistance and optical defects caused by agglomeration. By controlling the viscosity and cooperating with a leveling agent, a micro-nano composite rough surface is formed during spraying, and a multi-level reflection and radiation interface is constructed by using air interlayers and low refractive index particles.
[0077] In this application, the SiC@BN / TiB2 three-phase fiber skeleton is coupled with the matrix to form a direct heat conduction path through the inside and outside; the interwoven sheet-like calcium fluoride and calcium titanate / magnesium fluoride disperse heat flow and enhance toughness; micro-nano roughness and refractive index gradient improve solar reflection, and calcium fluoride and titanate together enhance atmospheric window radiation; holmium / ytterbium energy level conversion further outputs near-infrared heat from the environment; silane coupling agent and methylphenyl silicone resin construct a stable bond network to maintain the long-term integrity of the heat conduction network and structure, thereby achieving a synergistic enhancement of overall heat dissipation performance. Detailed Implementation
[0078] The technical solution of the present invention will be described in detail below with reference to specific embodiments. The embodiments described herein are specific implementations of the present invention and are used to illustrate the concept of the present invention; these descriptions are explanatory and exemplary and should not be construed as limiting the implementation of the present invention or the scope of protection of the present invention. In addition to the embodiments described herein, those skilled in the art can also adopt other obvious technical solutions based on the content disclosed in the claims and the specification of this application. These technical solutions include technical solutions that employ any obvious substitutions and modifications made to the embodiments described herein.
[0079] The chemical reagents used in the embodiments and comparative examples of this invention are all commercially available products and have not undergone further purification or processing.
[0080] Example 1
[0081] This embodiment provides a high thermal conductivity radiation cooling coating for 5G communication base station cabinets and its preparation method. The preparation method of the high thermal conductivity radiation cooling coating for 5G communication base station cabinets specifically includes the following steps:
[0082] S1: Polycarbosilane, boric acid, isopropyl titanate, and melamine are dissolved in a mixed solvent, wherein the mass ratio of polycarbosilane to boric acid is 18:1.4, the mass ratio of polycarbosilane to isopropyl titanate is 17.5:1.02, the mass ratio of polycarbosilane to melamine is 19:0.8, the mass ratio of DMF to THF is 1:1.15, and the mass ratio of polycarbosilane to DMF is 41:18. The solution is stirred at 420 rpm for 2.2 h at room temperature to obtain the initial spinning solution. After filtration, the precursor fiber membrane is spun and placed in air for 2.5 h before calcination. The first stage of calcination is carried out in air at a heating rate of 2.5 °C / min. The first stage of calcination was carried out at 255℃ for 2.2 hours. The second stage was conducted in an argon atmosphere at a flow rate of 210 mL / min and a heating rate of 5.5℃ / min, with the calcination temperature at 610℃ and the time being 0.55 hours. The third stage was conducted in an atmosphere of ammonia and argon at a volume ratio of 1:4, with a flow rate of 520 mL / min and a heating rate of 11℃ / min, with the calcination temperature at 1120℃ and the time being 1.1 hours. After natural cooling, a preliminary fiber skeleton was obtained. This skeleton was then immersed in an ethanol aqueous solution containing 0.55 wt% silane coupling agent for 28 minutes and dried at 125℃ for 0.55 hours to obtain a SiC@BN / TiB2 three-phase fiber skeleton.
[0083] S2: Prepare a calcium hydroxide dispersion with a calcium hydroxide to deionized water mass ratio of 7.6:205. Add titanium chloride under ice bath conditions and adjust the pH to 11.2 with potassium hydroxide, where the titanium chloride to calcium hydroxide mass ratio is 7.5:9.8. Perform a hydrothermal reaction at 185℃ for 9 hours. After cooling, centrifuge, wash with water, and vacuum dry to obtain star-shaped calcium titanate powder. Disperse magnesium nitrate and ammonium fluoride in deionized water with a magnesium nitrate, ammonium fluoride, and deionized water mass ratio of 3.2:1.1:42. Add calcium titanate powder to obtain reaction solution A, where the calcium titanate powder to magnesium nitrate mass ratio is 3.2:10.2. Stir at 72℃ for 1.1 hours. Filter, dry, and pulverize through a 210-mesh sieve. Calcine in air at 460℃ for 1.1 hours to obtain a calcium titanate / magnesium fluoride composite material.
[0084] S3: Calcium nitrate, holmium nitrate, and ytterbium nitrate were dispersed in deionized water to obtain a mixed dispersion, wherein the mass ratio of calcium nitrate, holmium nitrate, ytterbium nitrate, and deionized water was 12.0:0.29:1.65:105. Sodium fluoride was added at 62℃, wherein the mass ratio of calcium nitrate to sodium fluoride was 12.0:13.0. The mixture was stirred at 320 rpm for 2.2 h, centrifuged, washed, and dried to obtain a mixed precursor. The precursor was then crystallized in a quartz boat under an argon atmosphere at a gas flow rate of 320 mL / min, a heating rate of 5.5℃ / min, a crystallization temperature of 360℃, and a time of 1.1 h. After natural cooling, holmium / ytterbium co-doped calcium fluoride nanosheets were obtained.
[0085] S4: SiC@BN / TiB2 three-phase fiber skeleton and methylphenyl silicone resin were placed in a planetary vacuum stirred tank with a mass ratio of 31:55.5. The mixture was stirred at 520 rpm and -0.055 MPa for 5.5 min to obtain a premixed base solution. Calcium titanate / magnesium fluoride composite material and holmium / ytterbium co-doped calcium fluoride nanosheets were then added, with a mass ratio of 26:55.5 between the calcium titanate / magnesium fluoride composite material and methylphenyl silicone resin. The mass ratio of the base silicone resin was 8.5:55.5. After uniform dispersion, methyl phenyl silicone resin, KH-550, BYK-A530, FC-4430 and propylene glycol methyl ether acetate were added to obtain a pre-coating solution. The mass ratio of the methyl phenyl silicone resin, the added methyl phenyl silicone resin, KH-550, BYK-A530, FC-4430 and propylene glycol methyl ether acetate was 55.5:20:0.55:0.22:0.32:11. The viscosity was adjusted to 5.5 Pa·s. Vacuum degassing and filtration were performed to obtain a high thermal conductivity radiation cooling coating for 5G communication base station cabinets.
[0086] Example 2
[0087] This embodiment provides a high thermal conductivity radiation cooling coating for 5G communication base station cabinets and its preparation method. The preparation method of the high thermal conductivity radiation cooling coating for 5G communication base station cabinets specifically includes the following steps:
[0088] S1: Polycarbosilane, boric acid, isopropyl titanate, and melamine are dissolved in a mixed solvent, wherein the mass ratio of polycarbosilane to boric acid is 19:1.6, the mass ratio of polycarbosilane to isopropyl titanate is 19:1.05, the mass ratio of polycarbosilane to melamine is 18:0.85, the mass ratio of DMF to THF is 1:1.2, and the mass ratio of polycarbosilane to DMF is 38:19. The solution is stirred at 350 rpm for 2.5 h at room temperature to obtain the initial spinning solution. After filtration, the precursor fiber membrane is spun and placed in air for 3 h before calcination. The first stage of calcination is carried out in air at a heating rate of 3 °C / min. The first stage of calcination was carried out at 260℃ for 2.5 hours. The second stage was conducted in an argon atmosphere at a flow rate of 220 mL / min and a heating rate of 6℃ / min, with the calcination temperature at 620℃ for 0.6 hours. The third stage was conducted in an atmosphere of ammonia and argon at a volume ratio of 1:4, with a flow rate of 550 mL / min and a heating rate of 12℃ / min, with the calcination temperature at 1150℃ for 1.2 hours. After natural cooling, a preliminary fiber skeleton was obtained. This skeleton was then immersed in an ethanol-water solution containing 0.6 wt% silane coupling agent for 35 minutes and dried at 130℃ for 0.6 hours to obtain a SiC@BN / TiB2 three-phase fiber skeleton.
[0089] S2: Prepare a calcium hydroxide dispersion with a mass ratio of calcium hydroxide to deionized water of 7:210. Add titanium chloride under ice bath conditions and adjust the pH to 11.5 with potassium hydroxide, where the mass ratio of titanium chloride to calcium hydroxide is 7.8:10. Perform a hydrothermal reaction at 190℃ for 10 hours. After cooling, centrifuge, wash with water, and vacuum dry to obtain star-shaped calcium titanate powder. Disperse magnesium nitrate and ammonium fluoride in deionized water with a mass ratio of magnesium nitrate, ammonium fluoride, and deionized water of 3.3:1.2:45. Add calcium titanate powder to obtain reaction solution A, where the mass ratio of calcium titanate powder to magnesium nitrate is 3.3:10.5. Stir at 75℃ for 1.2 hours. Filter, dry, and pulverize through a 220-mesh sieve. Calcine in air at 470℃ for 1.2 hours to obtain a calcium titanate / magnesium fluoride composite material.
[0090] S3: Calcium nitrate, holmium nitrate, and ytterbium nitrate were dispersed in deionized water to obtain a mixed dispersion, wherein the mass ratio of calcium nitrate, holmium nitrate, ytterbium nitrate, and deionized water was 12.4:0.30:1.71:110. Sodium fluoride was added at 65°C, wherein the mass ratio of calcium nitrate to sodium fluoride was 12.4:13.5. The mixture was stirred at 350 rpm for 2.5 h, centrifuged, washed, and dried to obtain a mixed precursor. The precursor was then crystallized in a quartz boat under an argon atmosphere at a gas flow rate of 350 mL / min, a heating rate of 6°C / min, a crystallization temperature of 370°C, and a time of 1.2 h. After natural cooling, holmium / ytterbium co-doped calcium fluoride nanosheets were obtained.
[0091] S4: SiC@BN / TiB2 three-phase fiber skeleton and methylphenyl silicone resin were placed in a planetary vacuum stirred tank with a mass ratio of 32:56. The mixture was stirred for 6 minutes at 550 rpm and a vacuum of -0.06 MPa to obtain a premixed base solution. Calcium titanate / magnesium fluoride composite material and holmium / ytterbium co-doped calcium fluoride nanosheets were then added, with a mass ratio of 27:56 between the calcium titanate / magnesium fluoride composite material and methylphenyl silicone resin. The mass ratio of phenyl silicone resin is 9:56. After uniform dispersion, methyl phenyl silicone resin, KH-550, BYK-A530, FC-4430 and propylene glycol methyl ether acetate are added to obtain a pre-coating solution. The mass ratio of methyl phenyl silicone resin, added methyl phenyl silicone resin, KH-550, BYK-A530, FC-4430 and propylene glycol methyl ether acetate is 56:21:0.6:0.25:0.35:12. The viscosity is adjusted to 6 Pa·s. Vacuum degassing and filtration are performed to obtain a high thermal conductivity radiation cooling coating for 5G communication base station cabinets.
[0092] Example 3
[0093] This embodiment provides a high thermal conductivity radiation cooling coating for 5G communication base station cabinets and its preparation method. The preparation method of the high thermal conductivity radiation cooling coating for 5G communication base station cabinets specifically includes the following steps:
[0094] S1: Polycarbosilane, boric acid, isopropyl titanate, and melamine are dissolved in a mixed solvent, wherein the mass ratio of polycarbosilane to boric acid is 17.5:1.55, the mass ratio of polycarbosilane to isopropyl titanate is 18:1.0, the mass ratio of polycarbosilane to melamine is 17:0.75, the mass ratio of DMF to THF is 1:1.1, and the mass ratio of polycarbosilane to DMF is 40:17. The solution is stirred at 400 rpm for 2.0 h at room temperature to obtain the initial spinning solution. After filtration, the precursor fiber membrane is spun and placed in air for 2.0 h before calcination. The first stage of calcination is carried out in air at a heating rate of 2.0 °C / min. The first stage of calcination was carried out at 250℃ for 2.0 h. The second stage was conducted in an argon atmosphere at a flow rate of 200 mL / min and a heating rate of 5.0℃ / min, with a calcination temperature of 600℃ and a time of 0.5 h. The third stage was conducted in an atmosphere of ammonia and argon at a volume ratio of 1:4, with a flow rate of 500 mL / min and a heating rate of 10℃ / min, with a calcination temperature of 1100℃ and a time of 1.0 h. After natural cooling, a preliminary fiber skeleton was obtained. This skeleton was then immersed in an ethanol aqueous solution containing 0.5 wt% silane coupling agent for 30 min and dried at 120℃ for 0.5 h to obtain a SiC@BN / TiB2 three-phase fiber skeleton.
[0095] S2: Prepare a calcium hydroxide dispersion in which the mass ratio of calcium hydroxide to deionized water is 7.5:200. Add titanium chloride under ice bath and adjust the pH to 11.0 with potassium hydroxide, where the mass ratio of titanium chloride to calcium hydroxide is 7:9. Perform a hydrothermal reaction at 180℃ for 8 hours. After cooling, centrifuge, wash with water, and vacuum dry to obtain star-shaped calcium titanate powder. Disperse magnesium nitrate and ammonium fluoride in deionized water in a mass ratio of magnesium nitrate, ammonium fluoride, and deionized water of 3.1:1.15:40. Add calcium titanate powder to obtain reaction solution A, where the mass ratio of calcium titanate powder to magnesium nitrate is 2.9:10.0. Stir at 70℃ for 1.0 h, filter, dry, pulverize through 200 mesh, and calcine in air at 450℃ for 1.0 h to obtain calcium titanate / magnesium fluoride composite material.
[0096] S3: Calcium nitrate, holmium nitrate, and ytterbium nitrate were dispersed in deionized water to obtain a mixed dispersion, wherein the mass ratio of calcium nitrate, holmium nitrate, ytterbium nitrate, and deionized water was 11.8:0.28:1.60:100. Sodium fluoride was added at 60℃, wherein the mass ratio of calcium nitrate to sodium fluoride was 11.8:12.0. The mixture was stirred at 300 rpm for 2.0 h, centrifuged, washed, and dried to obtain a mixed precursor. The precursor was then crystallized in a quartz boat under an argon atmosphere at a gas flow rate of 300 mL / min, a heating rate of 5.0℃ / min, a crystallization temperature of 350℃, and a time of 1.0 h. After natural cooling, holmium / ytterbium co-doped calcium fluoride nanosheets were obtained.
[0097] S4: SiC@BN / TiB2 three-phase fiber skeleton and methylphenyl silicone resin were placed in a planetary vacuum stirred tank with a mass ratio of 30:55. The mixture was stirred at 500 rpm and a vacuum of -0.05 MPa for 5 min to obtain a premixed base solution. Then, calcium titanate / magnesium fluoride composite material and holmium / ytterbium co-doped calcium fluoride nanosheets were added, with a mass ratio of 25:55 between the calcium titanate / magnesium fluoride composite material and methylphenyl silicone resin. The mass ratio of phenyl silicone resin is 8:55. After uniform dispersion, methyl phenyl silicone resin, KH-550, BYK-A530, FC-4430 and propylene glycol methyl ether acetate are added to obtain a pre-coating solution. The mass ratio of methyl phenyl silicone resin, added methyl phenyl silicone resin, KH-550, BYK-A530, FC-4430 and propylene glycol methyl ether acetate is 55:19:0.50:0.20:0.30:10. The viscosity is adjusted to 5 Pa·s. Vacuum degassing and filtration are performed to obtain a high thermal conductivity radiation cooling coating for 5G communication base station cabinets.
[0098] Example 4
[0099] This embodiment provides a high thermal conductivity radiation cooling coating for 5G communication base station cabinets and its preparation method. The preparation method of the high thermal conductivity radiation cooling coating for 5G communication base station cabinets specifically includes the following steps:
[0100] S1: Polycarbosilane, boric acid, isopropyl titanate, and melamine are dissolved in a mixed solvent, wherein the mass ratio of polycarbosilane to boric acid is 17:1.55, the mass ratio of polycarbosilane to isopropyl titanate is 17:0.95, the mass ratio of polycarbosilane to melamine is 17.5:0.82, the mass ratio of DMF to THF is 1:1, and the mass ratio of polycarbosilane to DMF is 17:38. The solution is stirred at 350 rpm for 1.5 h at room temperature to obtain the initial spinning solution. After filtration, the precursor fiber membrane is spun and placed in air for 1.5 h before calcination. The first stage of calcination is carried out in air at a heating rate of 1 °C / min. The first stage of calcination was carried out at 240℃ for 1.5 h. The second stage was conducted in an argon atmosphere at a flow rate of 180 mL / min and a heating rate of 4℃ / min, with a calcination temperature of 580℃ and a time of 0.4 h. The third stage was conducted in an atmosphere of ammonia and argon at a volume ratio of 1:4, with a flow rate of 450 mL / min and a heating rate of 8℃ / min, with a calcination temperature of 1050℃ and a time of 0.8 h. After natural cooling, a preliminary fiber skeleton was obtained. This skeleton was then immersed in an ethanol aqueous solution containing 0.4 wt% silane coupling agent for 25 min and dried at 110℃ for 0.4 h to obtain a SiC@BN / TiB2 three-phase fiber skeleton.
[0101] S2: Prepare a calcium hydroxide dispersion in which the mass ratio of calcium hydroxide to deionized water is 7:190. Add titanium chloride under ice bath and adjust the pH to 10.5 with potassium hydroxide, where the mass ratio of titanium chloride to calcium hydroxide is 7:9. Perform a hydrothermal reaction at 170℃ for 6 hours. After cooling, centrifuge, wash with water, and vacuum dry to obtain star-shaped calcium titanate powder. Disperse magnesium nitrate and ammonium fluoride in deionized water in a mass ratio of magnesium nitrate, ammonium fluoride, and deionized water of 2.9:1:35. Add calcium titanate powder to obtain reaction solution A, where the mass ratio of calcium titanate powder to magnesium nitrate is 2.9:9.5. Stir at 65℃ for 0.8 hours. Filter, dry, and pulverize through 180 mesh. Calcium titanate / magnesium fluoride composite material is obtained by air calcination at 430℃ for 0.8 hours.
[0102] S3: Calcium nitrate, holmium nitrate, and ytterbium nitrate were dispersed in deionized water to obtain a mixed dispersion, wherein the mass ratio of calcium nitrate, holmium nitrate, ytterbium nitrate, and deionized water was 11.2:0.26:1.55:90. Sodium fluoride was added at 55°C, wherein the mass ratio of calcium nitrate to sodium fluoride was 11.2:11.5. The mixture was stirred at 250 rpm for 1.5 h, centrifuged, washed, and dried to obtain a mixed precursor. The precursor was then crystallized in a quartz boat under an argon atmosphere at a gas flow rate of 250 mL / min, a heating rate of 4°C / min, a crystallization temperature of 330°C, and a time of 0.8 h. After natural cooling, holmium / ytterbium co-doped calcium fluoride nanosheets were obtained.
[0103] S4: SiC@BN / TiB2 three-phase fiber skeleton and methylphenyl silicone resin were placed in a planetary vacuum stirred tank with a mass ratio of 28:54. The mixture was stirred at 450 rpm and a vacuum of -0.04 MPa for 4 min to obtain a premixed base solution. Calcium titanate / magnesium fluoride composite material and holmium / ytterbium co-doped calcium fluoride nanosheets were then added, with a mass ratio of 23:54 between the calcium titanate / magnesium fluoride composite material and methylphenyl silicone resin. The mass ratio of phenyl silicone resin is 7:54. After uniform dispersion, methyl phenyl silicone resin, KH-550, BYK-A530, FC-4430 and propylene glycol methyl ether acetate are added to obtain a pre-coating solution. The mass ratio of methyl phenyl silicone resin, added methyl phenyl silicone resin, KH-550, BYK-A530, FC-4430 and propylene glycol methyl ether acetate is 54:17:0.40:0.15:0.25:8. The viscosity is adjusted to 4 Pa·s. Vacuum degassing and filtration are performed to obtain a high thermal conductivity radiation cooling coating for 5G communication base station cabinets.
[0104] Comparative Example 1
[0105] This comparative example provides a high thermal conductivity radiation cooling coating for 5G communication base station cabinets. The difference from Example 1 is that in S4, the SiC@BN / TiB2 three-phase fiber skeleton is not added. Other operating steps and process parameters are exactly the same as in Example 1.
[0106] Comparative Example 2
[0107] This comparative example provides a high thermal conductivity radiation cooling coating for 5G communication base station cabinets. The difference from Example 1 is that calcium titanate / magnesium fluoride composite material is not added in S4, while other operating steps and process parameters are exactly the same as in Example 1.
[0108] Comparative Example 3
[0109] This comparative example provides a high thermal conductivity radiation cooling coating for 5G communication base station cabinets. The difference from Example 1 is that holmium / ytterbium co-doped calcium fluoride nanosheets are not added in S4. Other operating steps and process parameters are exactly the same as in Example 1.
[0110] The performance of the high thermal conductivity radiation cooling coatings for 5G communication base station cabinets in Examples 1-4 and Comparative Examples 1-3 was tested, and the specific process is as follows:
[0111] According to GB / T 25261-2018, the solar reflectance, near-infrared reflectance, hemispherical emissivity and thermal conductivity of the test samples were measured.
[0112] The test results are shown in Table 1.
[0113] Table 1: Performance Test Results of High Thermal Conductivity Radiation Cooling Coatings Used in 5G Communication Base Station Cabinets
[0114] Solar reflectance Near-infrared reflectance hemispherical emissivity Thermal conductivity (W / (m·K)) Example 1 0.93 0.89 0.92 2.4 Example 2 0.91 0.86 0.90 2.1 Example 3 0.89 0.87 0.91 2.0 Example 4 0.90 0.85 0.88 2.2 Comparative Example 1 0.86 0.82 0.85 1.2 Comparative Example 2 0.82 0.78 0.87 1.9 Comparative Example 3 0.84 0.81 0.87 1.8
[0115] As shown in Table 1, the test results of Example 1 and Comparative Example 1 reveal that without the addition of the SiC@BN / TiB2 three-phase fiber skeleton, the longitudinal phonon high-speed channel from the metal wall to the surface of the coating is disrupted. The interfacial thermal resistance changes from the original chemical bond coupling surface to a multi-stage jump of "filler-resin-filler," resulting in a decrease in the vertical thermal conductivity. Simultaneously, the absence of fiber roughness and its low-refractive-index "cavity" structure reduces the opportunities for multi-stage light scattering on the surface, leading to a decrease in solar and near-infrared reflectance. Silicon carbide, boron nitride, and titanium diboride themselves possess strong lattice radiation peaks in the atmospheric transmission window; their loss weakens mid-infrared emission and reduces hemispherical emissivity.
[0116] The test results from Example 1 and Comparative Example 2 show that without the addition of the calcium titanate / magnesium fluoride composite material, the loss of the angular multiple recombination scattering and refractive index step interface weakens diffuse reflection in the ultraviolet-near infrared region, leading to a decrease in solar reflectance. Near-infrared reflectance decreases further because calcium titanate contributes the most to the near-infrared region. The calcium titanate / magnesium fluoride composite material plays a "filler + bridging" role in the thermal conductivity network; its absence slightly reduces the thermal conductivity. In the mid-infrared non-primary emitting phase, the hemispherical emissivity also slightly decreases.
[0117] The test results from Example 1 and Comparative Example 3 show that without the addition of holmium / ytterbium co-doped calcium fluoride nanosheets, the dual effects of in-plane heat dissipation and energy level downshifting radiation are weakened. After the interlayer stacking of the sheet-like calcium fluoride is evacuated, lateral heat dissipation is reduced, and the thermal conductivity decreases. On the other hand, the energy transfer path between holmium and ytterbium disappears, and near-infrared heat is no longer converted to the atmospheric window band and discharged in the form of radiation, resulting in a decrease in near-infrared reflectance. The hemispherical emissivity also decreases due to the attenuation of mid-infrared spontaneous emission; overall solar reflectance decreases.
[0118] The above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the protection and disclosure scope of the present invention.
Claims
1. A method for preparing a high thermal conductivity radiation cooling coating for 5G communication base station cabinets, characterized in that, The preparation method includes: S1: Polycarbosilane, boric acid, isopropyl titanate and melamine are dissolved in a mixed solvent and stirred at room temperature to obtain a preliminary spinning solution. After filtration, a precursor fiber membrane is spun to obtain a precursor fiber membrane. The precursor fiber membrane is placed in air and then calcined and naturally cooled to obtain a preliminary fiber skeleton. The precursor fiber membrane is then impregnated in an ethanol-water solution of a silane coupling agent and dried to obtain a SiC@BN / TiB2 three-phase fiber skeleton. S2: Prepare calcium hydroxide dispersion, add titanium chloride under ice bath and adjust pH with potassium hydroxide, perform hydrothermal reaction, centrifuge after cooling, wash with water, and vacuum dry to obtain star-shaped calcium titanate powder; disperse magnesium nitrate and ammonium fluoride in deionized water, add calcium titanate powder to obtain reaction solution A, stir, filter, dry and pulverize, and air calcinate to obtain calcium titanate / magnesium fluoride composite material. S3: Calcium nitrate, holmium nitrate and ytterbium nitrate are dispersed in deionized water to obtain a mixed dispersion. Sodium fluoride is added, and the mixture is stirred to obtain a mixed precursor. The precursor is then placed in a quartz boat for crystallization and naturally cooled to obtain holmium / ytterbium co-doped calcium fluoride nanosheets. S4: SiC@BN / TiB2 three-phase fiber skeleton and methylphenyl silicone resin were placed in a planetary vacuum stirred tank and stirred to obtain a premixed base liquid. Calcium titanate / magnesium fluoride composite material and holmium / ytterbium co-doped calcium fluoride nanosheets were added and dispersed evenly. Then, methylphenyl silicone resin, KH-550, BYK-A530, FC-4430 and propylene glycol methyl ether acetate were added to obtain a pre-coating liquid. The viscosity was adjusted, vacuum degassing was performed, and filtration was carried out to obtain a high thermal conductivity radiation cooling coating for 5G communication base station cabinets.
2. The method for preparing a high thermal conductivity radiation cooling coating for 5G communication base station cabinets according to claim 1, characterized in that, In S1: The mass ratio of the polycarbosilane to boric acid is (17-19):(1.4-1.6); The mass ratio of the polycarbosilane to isopropyl titanate is (17-19):(0.95-1.05).
3. The method for preparing a high thermal conductivity radiation cooling coating for 5G communication base station cabinets according to claim 1, characterized in that, In S1: The mass ratio of polycarbosilane to melamine is (17-19):(0.75-0.85).
4. The method for preparing a high thermal conductivity radiation cooling coating for 5G communication base station cabinets according to claim 1, characterized in that, In S1: The mass ratio of DMF to THF in the mixed solvent is 1:(1-1.2); The mass ratio of the polycarbosilane to DMF is (17-19):(38-42).
5. The method for preparing a high thermal conductivity radiation cooling coating for 5G communication base station cabinets according to claim 1, characterized in that, In S2: The mass ratio of calcium hydroxide to deionized water in the calcium hydroxide dispersion is (7-7.8):(190-210); The mass ratio of titanium chloride to calcium hydroxide is (7-7.8):(9-10).
6. The method for preparing a high thermal conductivity radiation cooling coating for 5G communication base station cabinets according to claim 1, characterized in that, In S2: The mass ratio of magnesium nitrate, ammonium fluoride, and deionized water is (2.9-3.3):(1-1.2):(35-45); The mass ratio of calcium titanate powder to magnesium nitrate is (2.9-3.3):(9.5-10.5).
7. The method for preparing a high thermal conductivity radiation cooling coating for 5G communication base station cabinets according to claim 1, characterized in that, In S3: The mass ratio of calcium nitrate, holmium nitrate, ytterbium nitrate to deionized water is (11.2-12.4):(0.26-0.30):(1.55-1.71):(90-110).
8. The method for preparing a high thermal conductivity radiation cooling coating for 5G communication base station cabinets according to claim 1, characterized in that, In S3: The mass ratio of calcium nitrate to sodium fluoride is (11.2-12.4):(11.5-13.5).
9. The method for preparing a high thermal conductivity radiation cooling coating for 5G communication base station cabinets according to claim 1, characterized in that, In S4: The mass ratio of the SiC@BN / TiB2 three-phase fiber skeleton to methylphenyl silicone resin is (28-32):(54-56); The mass ratio of the calcium titanate / magnesium fluoride composite material to methylphenyl silicone resin is (23-27):(54-56); The mass ratio of the holmium / ytterbium co-doped calcium fluoride nanosheets to methylphenyl silicone resin is (7-9):(54-56); The mass ratio of the methyl phenyl silicone resin, the supplemented methyl phenyl silicone resin, KH-550, BYK-A530, FC-4430 to propylene glycol methyl ether acetate is (54-56):(17-21):(0.40-0.60):(0.15-0.25):(0.25-0.35):(8-12).
10. A high thermal conductivity radiation cooling coating for 5G communication base station cabinets prepared by the preparation method according to any one of claims 1-9.
Citation Information
Patent Citations
Method for preparing heterogeneous nuclear shell structure CaF2:20Yb, 2Ho@NaXF4 nanocrystalline
CN103289701A
Industrialized production method of high-purity nano calcium titanate
CN108439461A
High-strength low-thermal-conductivity SiC-TiO2 nanofiber aerogel and preparation method thereof
CN119735450A
Anti-oxidation coating for anode carbon block and preparation method of anti-oxidation coating
CN120699459A
Insulator and connector made of thermoplastic hydrocarbon polymer
JP1999162551A